KETERAMPILAN MATEMATIKA SISWA DALAM MENGGUNAKAN APLIKASI MAPLE PADA MATERI MATRIKS - Syamsuddin, Syamsuddin; Ahmad, Herlina (Fakultas Keguruan dan Ilmu Pendidikan Univ. Al Asyariah Mandar Sulbar, 2023)
This research is qualitative research which aims to describe students' mathematical skills in using the maple application. The subjects of this research were 32 students of Mega Link Majene Vocational School Class X DKV. The instruments used in this research were performance assessment tests and closed interview sheets. Mathematics performance assessment tests on skills in using the maple application, especially on matrix material, were carried out through practical methods to assess students' skill processes. Closed interviews were carried out after students took the performance assessment test. Based on the results of the research analysis, it was found that there were 3 students who were at the superior criteria (level 4). There are 17 students who are at the skilled criteria (level 3). There are 12 students who are in the quite skilled criteria (level 2). There are no students who fall under the criteria of less skilled (level 1) and unskilled (level 0).